PERBEDAAN HASIL BELAJAR STATIKA BERDASARKAN STRATEGI PEMBELAJARAN INKUIRI DAN KONVENSIONAL SISWA KELAS X PROGRAM KEAHLIAN TEKNIK GAMBAR BANGUNAN SMK NEGERI 1 BUKITTINGGI - 366-373 , Ade Dwinta (CIVED, 2014)
ABSTRACT   This study aims to determine whether there is any effect of the application of inquiry learning strategies on student learning outcomes in subjects in class X statics Architecture Engineering SMK Negeri 1 Bukittinggi .This research is an experimental study , namely Pre - Experimental Designs. The population in this study were all students of class X in Architecture Engineering skills program at SMK Negeri 1 Bukittinggi school year 2013/2014. Based on the results of a comparative analysis on the obtained value of F test of homogeneity = 11.23 and F table = 2.05. These results show that the F value > F, meaning both groups of student learning outcomes data have variants that are not homogeneous. Furthermore, the test of homogeneity of variance obtained is not homogeneous and n1 ≠ n2 , then used t-tests with a separated variant . From the analysis of the data obtained and the price of t = 3.2 t table = 1.968 at 0.05 level. From these calculations it appears that t count > t table , this means that the hypothesis proposed in the study ( H0 ) is rejected. Keywords: Effects , Inquiry Learning Strategy , Learning Outcomes